What is the association of elite sporting activities with the development of hip osteoarthritis? - Vigdorchik, J. M.; Nepple, J. J.; Eftekhary, N.; Leunig, M.; Clohisy, J. C. (The American Journal of Sports Medicine, 2017)
Background: Male athletes participating in certain elite sporting activities may be at an increased risk for development of hip osteoarthritis (OA) later in life. However, the strength of the association of participation in sporting activities with the increased risk of hip OA has not been well summarized. Purpose: To investigate the association of certain high-impact sporting activities with the risk of development of hip OA in elite athletes by conducting a systematic review of the available literature. Study Design: Systematic review; Level of evidence, 3. Methods: PubMed, Cochrane, and EMBASE databases were searched to identify all potential studies. Eleven studies met the inclusion criteria, which included participation in elite-level sporting activities, greater than 50% male athletes in the study population, diagnosis of hip OA by radiograph, hospital admission or total hip arthroplasty (THA), and greater than 80% follow-up. Exclusion criteria were recreational sporting activities, primarily female cohorts as there was a dearth of available literature on the topic, and self-reported symptoms without radiographic confirmation of diagnosis. Most studies were with European athletes, where elite-level was defined as involvement in national- or professional-level competition. Results: Participation across elite-level impact sports was associated with increased risk of development of hip OA when compared with matched controls (odds ratio, 1.8-8.7). Twelve of 15 studies reviewed demonstrated an odds ratio of 1.8 or greater of developing hip OA in elite-level athletes. Handball was associated with the highest rate of OA of any sport, nearly 5 times that of matched controls. Soccer players demonstrated between 2 and 9 times increased risk of hip OA as defined by radiography or THA. Hockey players demonstrated 2 to 3 times increased risk of hip OA (THA or hospital admission). Five studies investigating the association of competitive long-distance running with hip OA demonstrated inconsistent results. Conclusion: Currently available literature suggests that male athletes participating in elite impact sports (soccer, handball, track and field, or hockey) are at an increased risk of developing hip OA, while those participating in high-level long-distance running do not have a clearly elevated risk. Further research is warranted to elucidate the pathomechanics of development of hip OA in these patients.